2016
DOI: 10.1158/0008-5472.can-15-1553
|View full text |Cite|
|
Sign up to set email alerts
|

The E3-ligase E6AP Represses Breast Cancer Metastasis via Regulation of ECT2-Rho Signaling

Abstract: Metastatic disease is the major cause of breast cancer-related death and despite many advances, current therapies are rarely curative. Tumor cell migration and invasion require actin cytoskeletal reorganization to endow cells with capacity to disseminate and initiate the formation of secondary tumors. However, it is still unclear how these migratory cells colonize distant tissues to form macrometastases. The E6-associated protein, E6AP, acts both as an E3 ubiquitin-protein ligase and as a coactivator of steroi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…E6AP was recently reported to possess anti‐metastasis activity in breast cancer cells . In line with this, we confirmed that E6AP physically interacted and colocalized with ENO1 both in vitro as well as in cell that actually is a prerequisite for an E3 ligase for targeting its substrates for ubiquitin‐mediated proteasome degradation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…E6AP was recently reported to possess anti‐metastasis activity in breast cancer cells . In line with this, we confirmed that E6AP physically interacted and colocalized with ENO1 both in vitro as well as in cell that actually is a prerequisite for an E3 ligase for targeting its substrates for ubiquitin‐mediated proteasome degradation.…”
Section: Discussionsupporting
confidence: 87%
“…In a recent study E6AP was shown to act as a tumor suppressor in non‐small cell lung cancer by maintaining INK4/ARF expression levels . Mansour et al showed that E6AP suppressed breast cancer invasiveness, colonization, and metastasis in mice as well as in breast cancer patients while E6AP loss was associated with poor prognosis, particularly for basal breast cancer . They further showed that E6AP regulated actin cytoskeletal remodeling via regulation of Rho GTPases by negatively regulating ECT2, a Guanine exchange Factor (GEF) required for activation of Rho GTPases.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors, however, may be related 17. Mansour et al reported E6AP (E3 ligase E6-associated protein) serves as a suppressor of metastasis and was a negative regulator of ECT2 in breast cancers, and may be a therapeutic target for patients with metastatic breast cancer 13. In a follow-up study, we will investigate the expression of ECT2 in breast cancer in vitro and in vivo, hopefully to find out the mechanism of ECT2 in the progression of breast cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Besides, ECT2 was found in a variety of human tumors, such as lung cancer, esophageal cancer, and pancreatic cancer . Mansour's study showed that ECT2 was a marked inhibitor in the progression of metastatic breast cancer . According to Jin et al the up‐regulated ECT2 in gastric cancer was correlated with lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…22 Mansour's study showed that ECT2 was a marked inhibitor in the progression of metastatic breast cancer. 21 According to Jin et al 22 the up-regulated ECT2 in gastric cancer was correlated with lymph node metastasis. However, the function of ECT2 in HCC cells is scarcely documented.…”
Section: Introductionmentioning
confidence: 99%